AMMONIA: A SILENT ENEMY IN POULTRY FARMING - Bandeira, Jéssica de Torres; Morais, Renato Souto Maior Muniz de; Rocha, Priscilla Maria Cavalcante; Silva, Alex Laurindo da; Pereira, Iza Jamile Moreira Vilar; Santana, Anderson Gabriel Farias de; Souza, Francisco de Assis Leite; Evêncio-Neto, Joaquim (Arquivos de Ciências Veterinárias e Zoologia da UNIPAR, 2025)
Ammonia (NH3) is the most critical air pollutant among those related to animal husbandry, especially poultry farming. This gas can cause injuries to humans and animals, particularly in the respiratory tract, and even inflammation in the trachea and lungs. However, the damage extends further, affecting the cornea, liver, and intestines as well. NH3 is also considered responsible for increasing serum levels of inflammatory mediators and uric acid, in addition to causing changes in the DNA of breast muscle cells, thereby reducing their quality. Therefore, a comprehensive and up-to-date understanding of the effects of this gas is crucial for all those involved in poultry farming.